Official online brand stores or online marketplaces? Exploring innovation in consumer intentions - Yu-Bing Wang; Pin Yin Chen (Journal of Innovation & Knowledge (JIK), 2024)
Official online stores and online marketplaces present distinct challenges and opportunities for retail brands, impacting their control over the customer experience, pricing, and brand presentation. Understanding consumer intentions in online channel selection is crucial, especially given the rise of online shopping and the impact of the COVID-19 pandemic on consumer behavior. This study explores the factors influencing channel selection intention within official online stores and online marketplaces, focusing on customers who have purchased Apple electronics. A quantitative questionnaire facilitated data collection, resulting in responses from 490 individuals and 606 samples. Those who shopped through both channels were requested to complete the questionnaire twice. The respondents were divided into two groups based on their purchasing experience, and structural equation modeling was employed for hypothesis testing. In official online stores, cross-channel searching negatively impacts channel selection intention, whereas brand loyalty and channel pricing advantage have positive effects. In contrast, no significant relationships between these variables were observed in online marketplaces. Channel satisfaction was found to positively influence channel selection intention across official online stores and online marketplaces, while perceived risk demonstrated a negative impact. Based on these findings, several recommendations are proposed to aid in developing effective sales channel strategies.
Keywords: M30; M39; 650; Official online store; Online marketplace; Channel selection intention; Brand loyalty; Cross-channel searching; Channel price advantage; Channel satisfaction; Perceived risk